Law and objectivity - Greenawalt, Kent 1936- (Oxford Univ. Pr., 1992)
Greenawalt begins by considering skeptical views about the meaning of language. Inquiring into the language of legal standards and whether it can yield correct answers to legal problems, he explores how the language of authoritative standards can indicate a single correct resolution in some cases, but not in others